Occurrence of enteric parasites in populations of Quiscalus lugubris (Aves: Passeriformes, Icteridae) of urban semiarid of Falcon state, Venezuela - Cazorla Perfetti, Dalmiro (2017)
Intestinal parasites in passerine birds can potentially have zoonotic importance. A study was conducted to determine the occurrence of intestinal parasites in feces of Carib Grackle, Quiscalus lugubris, populations (Aves, Passeriformes: Icteridae), in the city of Coro, Falcon State, Venezuela. Parasitological examination of the samples (n=156) was conducted by applying the direct smear, Willis-Molloy (NaCl) and Faust (zinc sulphate) flotation methods, spontaneous sedimentation in tube technique and Kinyoun staining. One or up to three intestinal protozoa, helminths and acanthocephalan taxa were detected in 109 (69.9%) fecal samples. Isospora spp (59.0%), Criptosporidium spp (37.8%) and the spiny-headed worm Mediorhynchus spp (6.4%) were the most frequent enteric parasites. All of the detected parasites are new records for Q. lugubris in Venezuela.